2010
DOI: 10.1530/eje-09-0366
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between FSH, inhibin B, anti-Mullerian hormone, and testosterone during long-term treatment with the GnRH-agonist histrelin in patients with prostate cancer

Abstract: Objectives: Medical castration with long-acting GnRH-agonist (GnRHa) is a well-established treatment for metastatic prostate cancer. Our aim was to explore the relationships between FSH, inhibin B, antiMullerian hormone (AMH), and testosterone during treatment with an implant releasing GnRHa. Design: Analysis of hormone levels in frozen serum samples. Methods: Ten patients aged 77G7 (meansGS.E.M.) years with prostate cancer were treated with the GnRHa histrelin for at least a year. Two weeks prior to insertion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…A dysynchrony between LH and testosterone occurs in elderly men [29]. Consequently, alteration of the gonadal-pituitary axis may also be important for age-related changes in Sertoli cell hormones, as FSH regulates InhB [30] and as AMH is putatively under the control of GnRH [31]. LH and FSH exhibit a circhoral rhythm in men [32], whereas AMH has a half-life of greater than a day [33].…”
Section: Discussionmentioning
confidence: 99%
“…A dysynchrony between LH and testosterone occurs in elderly men [29]. Consequently, alteration of the gonadal-pituitary axis may also be important for age-related changes in Sertoli cell hormones, as FSH regulates InhB [30] and as AMH is putatively under the control of GnRH [31]. LH and FSH exhibit a circhoral rhythm in men [32], whereas AMH has a half-life of greater than a day [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, when a GnRH agonist implant was also administered for a year, FSH and testosterone initially fell (again with no change in AMH), but a late and prolonged rise in FSH (from one month onwards with FSH rising back towards baseline levels) with sustained suppression of testosterone, was accompanied by a rise in AMH. The authors concluded that FSH has a role in regulating AMH in the absence of testosterone action [29]. In our study, there was no secondary rise in FSH back towards baseline and this may reflect the different therapies used to achieve FSH suppression, being a GnRH agonist implant in Eldar-Geva's group and exogenous testosterone therapy in our subjects.…”
Section: Does Sustained Rise In Fsh Have a Role In Modulating Amh?mentioning
confidence: 44%
“…An informative study by Eldar-Geva et al [29] reports treating 10 men with antiandrogens with a subsequent rapid rise in serum testosterone and FSH (as expected) and AMH did not change during this phase of therapy. However, when a GnRH agonist implant was also administered for a year, FSH and testosterone initially fell (again with no change in AMH), but a late and prolonged rise in FSH (from one month onwards with FSH rising back towards baseline levels) with sustained suppression of testosterone, was accompanied by a rise in AMH.…”
Section: Does Sustained Rise In Fsh Have a Role In Modulating Amh?mentioning
confidence: 62%
See 1 more Smart Citation
“…Hasil penelitian lain pada manusia menunjukkan bahwa level serum inhibin B berkorelasi erat dengan level serum FSH dan konsentrasi testosteron (Raivio et al, 2000). Selain itu, serum inhibin B berkorelasi signifikan dengan konsentrasi spermatozoa dan berkorelasi negatif dengan konsentrasi FSH (Eldar-Geva et al, 2010).…”
Section: Hasil Dan Pembahasanunclassified